NAMA KELUARGA DALAM BAHASA INGGRIS DAN BAHASA KAILI (ANALISIS KONTRASTIF) - Kalesaran, Eirene Elshara Pingkanawulan (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This study is an attempt to describe and analyze family names in English and Kaili language. In this research, the writer uses Hickerson’s theory and McVetty’s concept. The aims of this research are to identify and classify and to find out the kinds and meanings of the family names in English and in Kaili language and to contrast them, in order to find out similarities and the differences. To contrast the family names will use the theory base on Lado. The English data were taken from English textbooks and website, whereas Kaili language were elicited by interviewing ten informants and based on Kaili language textbooks. The informants were selected by using Nida’s theory. The results show that five types of the English family names have (1) patronymic family names, (2) family names referring to place of origin or locality, (3) family names referring to occupation (4) family names referring to nickname as well as family names adopted from given name, and (5) family names referring to identity of its family; whereas Kaili family names have (1) family names referring to place of origin or locality, (2) family names referring to occupation, (3) family names referring to nickname as well as adopted from given name, and (4) family names referring to identity of its family. Keywords : Family Names, English and Kaili Language, Contrastive Analysis